A Rare Case of Near Complete Regression of a Large Cervical Disc Herniation without Any Intervention Demonstrated on MRI. (6th January 2014) - Mahajan, Parag Suresh; Al Moosawi, Nawal M.; Hasan, Islam Ali
Abstract : There are very few reported cases of regression of large cervical disc herniation without any intervention—the so-called spontaneous regression, demonstrated using MRI. We report a rare and interesting case of MRI that demonstrated near complete regression of a large herniated cervical intervertebral disc, without any surgical treatment.